Study of tobacco use and related factors among adolescent students of secondary school in south-eastern region of Rajasthan, India - Meena, Rahul; Meena, Shivraj; Mittal, Deepika; Meena, Neelam (International Journal Of Community Medicine And Public Health, 2017)
Background: this study aims to estimate the level of tobacco use among school-going adolescents and also identify the factors that influence youth to use tobacco. Identification of the factors responsible for initiating tobacco use among adolescents will be useful for identifying the most effective interventions to prevent youths from taking up the tobacco habit. Methods: This was a cross-sectional study which was conducted in adolescent students of grade 8, 9 and 10 from secondary schools within Kota city of Rajasthan. 2032 questionnaires (1228 from government schools and 804 from non-government schools) were included in the analysis. Results: About seven in ten (71.0%) adolescent students were living in the family where at least one member uses tobacco. Nearly one-third (31.0%) of the adolescent students were having good knowledge and less than half (42.7%) were having some knowledge about the hazards of tobacco use. About one third (32.3%) of adolescent students were exposed to pro-tobacco advertisements. Conclusions: Immediate action to reduce adolescents’ exposure to environmental tobacco smoke is necessary. Prohibiting tobacco use at school and monitoring the high-risk behaviors of adolescents in school is necessary. Strictly Announcing schools and other public places as “tobacco-free places” will help to minimize the exposure to tobacco smoke. It also helps to change social norms and ultimately to minimize the use of tobacco.